As pesquisas sobre avaliação na Educação Infantil com crianças de zero a três anos de idade: concepções, práticas avaliativas e o protagonismo das crianças bem pequenas - Brito, Marilene de (2022)
This research is linked to the Line of Knowledge and Educational Practices, of the Graduate Program in Education, Faculty of Education, Federal University of Uberlândia. It presents, as an object of study, the evaluation in Early Childhood Education, with children from zero to three years old, in the context of day care centers. As a general objective, it sought to investigate academic research that discusses the evaluation practices carried out in day care centers with babies and very young children, from zero to three years old, their implications and possibilities in the teaching-learning process. The work also sought to analyze the conceptions of child(ren), childhood(s), day care/early education, educational assessment, formative assessment in Early Childhood Education and their relationships in the selected researches; highlight the role of evaluation and the way in which it is present in Education for children from zero to three years of age; and finally, identify and discuss the role and protagonism of children in the evaluation process. The methodology used was based on state-of-the-art bibliographical research on CAPES (Catalog of Theses & Dissertations, Coordination for the Improvement of Higher Education Personnel) and BDTD (Brazilian Digital Library of Theses and Dissertations) platforms, through of the survey of academic productions on the subject. As a problem, we sought to understand the conception of evaluation that is presented in the age group studied; the role of assessment in this teaching-learning process; how the evaluative practices carried out in day care centers with children from zero to three years of age take place and the role played by these children in the educational process and in the evaluative practices. We also sought to understand the role of children in the evaluation process. The results obtained made it possible to discuss three themes, which were: The conceptions of evaluation in Early Childhood Education; Evaluative practices in Early Childhood Education; and the protagonism of very young children in the evaluation process. The results revealed that in Early Childhood Education, the effective practice of formative assessment by the teachers is necessary; The subject of evaluation in Early Childhood Education has been gaining space in the field of Science, as an object of investigation, but there is still little research, focused on the study of evaluation with babies and very young children, especially that show their protagonism and participation in the evaluation processes. Another aspect refers to the need to give the day care center its own identity, which, from its historical course to the present day, carries with it the charitable character and vision. Another aspect refers to the need to give the day care center its own identity, which, from its historical course to the present day, carries with it the charitable character and vision. The research defends the recognition of the day care center as a space for educating and caring, with evaluative practices consistent with the needs and specificities of each age group, so that a formative evaluation is put into practice, which considers and enables the participation of children, as well as the teaching reflection of their actions, in order to contribute and favor the monitoring of children's learning, making their protagonism visible.